Supply Chain Integration and Sustainable Organizational Performance: Moderating Role of Blockchain Adoption - Tipon Tanchangya; Kazi Omar Siddiqi; Kamron Naher; Miguel Angel Esquivias; Naimul Islam; Shishir Das; Shajib Chowdaury; Sheikh Fariha (Ital Publication, 2026)
This research aims to investigate the impact of supply chain integration (SCI) on sustainable organizational performance (SOP). SCI includes supply chain agility (SCA), supply chain agility visibility (SCV), and supply chain agility flexibility (SCF), which examined the effect on SOP and green supply chain management (GSCM). This query also examines the moderating role of blockchain adoption (BA) on the relationship between SCI and GSCM, and the mediating role of GSCM in the relationship between SCI and SOP. A purposive sampling approach is used to collect data from 364 blockchain adopters who are also directly connected to SCI within the Bangladeshi manufacturing sector. The dataset is analyzed by the Structural Equation Model (SEM). The results revealed a substantial impact of SCA, SCV, and SCF on SOP. Additionally, GSCM plays a significant role in SCA, SCF, and SOP, whereas there is no significant effect of GSCM on SCV and SOP. In the moderation analysis, BA significantly and positively moderates the relationships among SCA, SCF, and GSCM. However, no significant effect of BA was found between SCV and GSCM. This research adds value to the existing literature on the Bangladeshi manufacturing sector by integrating SCA, SCV, and SCF, which were examined separately in previous studies.